Use and cost of home health agency services under Medicare - Ruther, Martin (CENTERS for MEDICARE & MEDICAID SERVICES, 1988)
Presented are 1986 data and trend data (1974-86) on the use and cost of home health agency services rendered to aged and disabled Medicare beneficiaries. Since 1974, reimbursements for these services have grown more rapidly than overall Medicare expenditures. From 1974 to 1986, Medicare expenditures for these services increased from $141 million to $1.8 billion, an average annual rate of 24 percent. HHA reimbursements, however, continue to represent only a small proportion (3.6 percent in 1986) of all Medicare expenditures.